Air pollutants cause release of hydrogen peroxide and interleukin‐8 in a human primary nasal tissue culture model. Issue 12 (14th November 2014) - Cho, Do‐Yeon; Le, Wei; Bravo, Dawn T.; Hwang, Peter H.; Illek, Beate; Fischer, Horst; Nayak, Jayakar V.
<x xml:space="preserve">Abstract</x> Background A component of primary innate defense of the nasal mucosa against inhaled pathogens includes continuous, low‐level release of hydrogen peroxide (H2O2) into luminal secretions. Epidemiologically, an association exists between poor air quality and increased prevalence of sinonasal disease. To understand the effects of particulate matter (PM) in nasal mucosa, we studied the release of H2O2 and interleukin 8 (IL‐8) after PM exposure. Methods Human nasal specimens were collected from surgery and cultured in serum‐free growth medium. Cell integrity and recovery during culture was monitored by lactate dehydrogenase (LDH) release into the medium. Cultures were exposed to PM for 24 hours in the presence/absence of diphenyleneiodonium sulfate (DPI; a nicotinamide adenine dinucleotide phosphate [NADPH] oxidase inhibitor). Luminex cytokine and Amplex‐Red H2O2 assays were performed. Results LDH levels dropped rapidly within 2 days, indicative of stabilization and cell recovery after harvest. All cultures released H2O2 into the medium. Exposure to PM (20 μg/cm2) increased H2O2 levels significantly (94.6 ± 7.7 nM) compared to untreated controls (55.8 ± 4.0 nM; p = 0.001). PM‐induced H2O2 production was partially inhibited by DPI (80.1 ± 3.8nM), indicating that cellular NADPH oxidase may be a primary source of H2O2 production. Exposure to PM increased IL‐8 levels in a dose‐dependent fashion (control = 2301 ± 412 MFI; 20 μg/cm2 = 5002 ± 1327 MFI; 40 μg/cm2 = 8219 ± 1090 MFI; p = 0.022). Conclusion PM increases the quantity of H2O2 released by nasal epithelial cells, indicating that PM can contribute to oxidative stress in part by activating a normal cellular defense mechanism. Exposure to PM resulted in elevated IL‐8 levels and mucin production in explants. Efforts to reduce airborne PM may lead to reduced H2O2 and mucin production in sinonasal epithelium.